1998
DOI: 10.1046/j.1365-2044.1998.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐choice examinations: adopting an evidence‐based approach to exam technique

Abstract: SummaryNegatively marked multiple-choice questions (MCQs) are part of the assessment process in both the Primary and Final examinations for the fellowship of the Royal College of Anaesthetists. It is said that candidates who guess will lose marks in the MCQ paper. We studied candidates attending a pre-examination revision course and have shown that an evaluation of examination technique is an important part of an individual's preparation. All candidates benefited substantially from backing their educated gues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…The results of the present study support the advice given by Hammond et al (1998) that students should guess if they have partial knowledge.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of the present study support the advice given by Hammond et al (1998) that students should guess if they have partial knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…(Budescu & Bar-Hillel, 1993;Hammond et al, 1998), the results of this study suggest that this strategy may be detrimental for students' performance.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Using the Kolmogorov-Smirnov normality test, we found that the marks' distribution at MCQ tests followed the normal law, which signifies that the computerized evaluation was objective, while the marks distribution at oral assessment did not fulfill this property, which means a certain degree of subjectivism in examiner's notation, revealed also in previous studies. Thus the following advantages of the MCQ assessment type were revealed, namely the increased objectivity, ease of filling and the speed of obtaining the results, which explains the students' preference, fact that was also noted by Hammond, McIndoe, Sansome, andSpargo (1998) andBrady (2005). Higgins and Tatham (2003) and Ventouras et al (2010) point out the advantages of MCQ test and especially the disadvantages, citing the risk of dumbing down.…”
Section: Resultsmentioning
confidence: 92%